A Zero‐Dimensional Organic Seesaw‐Shaped Tin Bromide with Highly Efficient Strongly Stokes‐Shifted Deep‐Red Emission. Issue 4 (21st December 2017) - Zhou, Chenkun; Lin, Haoran; Shi, Hongliang; Tian, Yu; Pak, Chongin; Shatruk, Michael; Zhou, Yan; Djurovich, Peter; Du, Mao‐Hua; Ma, Biwu
Abstract: The synthesis and characterization is reported of (C9 NH20 )2 SnBr4, a novel organic metal halide hybrid with a zero‐dimensional (0D) structure, in which individual seesaw‐shaped tin (II) bromide anions (SnBr4 2− ) are co‐crystallized with 1‐butyl‐1‐methylpyrrolidinium cations (C9 NH20 + ). Upon photoexcitation, the bulk crystals exhibit a highly efficient broadband deep‐red emission peaked at 695 nm, with a large Stokes shift of 332 nm and a high quantum efficiency of around 46 %. The unique photophysical properties of this hybrid material are attributed to two major factors: 1) the 0D structure allowing the bulk crystals to exhibit the intrinsic properties of individual SnBr4 2− species, and 2) the seesaw structure enabling a pronounced excited state structural deformation as confirmed by density functional theory (DFT) calculations. Abstract : Little red seesaw : A zero‐dimensional organic–inorganic hybrid containing a seesaw‐shaped tin bromide species is reported. It exhibits a highly efficient strongly Stokes‐shifted broadband deep‐red emission, which is a result of excited‐state structural deformation from a seesaw to a flattened tetrahedron structure.